TGFβ-Signaling and FOXG1-Expression Are a Hallmark of Astrocyte Lineage Diversity in the Murine Ventral and Dorsal Forebrain - Weise, Stefan Christopher; Villarreal, Alejandro; Heidrich, Stefanie; Dehghanian, Fariba; Schachtrup, Christian; Nestel, Sigrun; Schwarz, Jennifer; Thedieck, Kathrin; Vogel, Tanja (Frontiers in Cellular Neuroscience, 2018)
Heterogeneous astrocyte populations are defined by diversity in cellular environment, progenitor identity or function. Yet, little is known about the extent of the heterogeneity and how this diversity is acquired during development. To investigate the impact of TGF (transforming growth factor) β-signalling on astrocyte development in the telencephalon we deleted the TGFBR2 (transforming growth factor beta receptor 2) in early neural progenitor cells in mice using a FOXG1 (forkhead box G1)-driven CRE-recombinase. We used quantitative proteomics to characterise TGFBR2-deficient cells derived from the mouse telencephalon and identified differential protein expression of the astrocyte proteins GFAP (glial fibrillary acidic protein) and MFGE8 (milk fat globule-EGF factor 8). Biochemical and histological investigations revealed distinct populations of astrocytes in the dorsal and ventral telencephalon marked by GFAP or MFGE8 protein expression. The two subtypes differed in their response to TGFβ-signalling. Impaired TGFβ-signalling affected numbers of GFAP astrocytes in the ventral telencephalon. In contrast, TGFβ reduced MFGE8-expression in astrocytes deriving from both regions. Additionally, lineage tracing revealed that both GFAP and MFGE8 astrocyte subtypes derived partly from FOXG1-expressing neural precursor cells.